Problem of National Identity and Ways of its Resolution in Works of Adyghe and Karachay-Balkarian Authors - Betuganova (Kanametova), Yelena; Uzdenova, Fatima; Dodueva, Aminat; Khubolov, Sahadin (Journal of History Culture and Art Research, 2019)
In modern times humanity is facing a crisis in many spheres, the spiritual and moral one being most urgent. Resort to the ethnocultural tradition based on the ethical-aesthetic ideas, local customary practices and traditional (adat) laws seems most effective to overcome the crisis phenomena. In this connection, the preservation of ethnocultural identity comes to the fore. The leading feature of modern literature is the interest to ethnic self-identity as a defensive reaction to globalization and leveling of the individual’s self-categorization. Emotive prose and poetry by Adyghe and Karachay-Balkarian authors have been analyzed in the article with the view of determining the forms of manifestation of the heroes’ ethnic identity, establishing the role of traditional concepts and archetypical ideas in the formation of the ethnic self-categorization and the development of their worldview.